Accessing and Processing MEG Signals in Real-Time: Emerging Applications and Enabling Technologies - Foldes, Stephen; Wang, Wei; Collinger, Jennifer; Li, Xin; Zhang, Jinyin; Sudre, Gustavo; Bagić, Anto; Weber, Douglas J. (IntechOpen, 2011)
None